Application of historic datasets to understanding open solar flux and the 20th-century grand solar maximum. 1. Geomagnetic, ionospheric, and sunspot observations - Lockwood, Mike; Owens, Mathew J.; Barnard, Luke A.; Scott, Chris J.; Frost, Anna M.; Yu, Bingkun; Chi, Yutian (Frontiers in Astronomy and Space Sciences, 2022)
We update annual mean reconstructions of near-Earth interplanetary conditions and (signed) open solar flux $F_S$ for the past 186 years. We add observations for solar cycle 24 to refine the regressions and we improve the allowance for orthogardenhose and folded (a.k.a., switchback) heliospheric flux from studies using strahl electrons. We also improve the allowance made for the annual mean gardenhose angle of the interplanetary magnetic field. We use both multiple regression with IMF $B$ and solar wind speed $V_{SW}$ and linear regression with the function ${BV}_{SW}^n$ and show that the latter gives correlations that are not significantly lower than those for the former. We carry out a number of tests of the geomagnetic indices used, of which by far the most important is that all four usable pairings of indices produce almost identical results for $B$, $V_{SW}$ and $F_S$. All reconstructions are given full ${2σ}$ uncertainties using a Monte-Carlo technique that generates an ensemble of 1 million members for each pairing of indices. The long-term variations of near-Earth interplanetary field $B$ and open solar flux $F_S$ are shown to match that of the international sunspot numbers closely, but $V_{SW}$ shows a considerably different variation. This result explains why it is that, of the two peaks of 20$^{th}$-century grand solar maximum, the range geomagnetic indices give a larger second peak whereas the diurnal variation indices give a first peak that is the larger, as it is for sunspots. We find the rise in solar cycle averages of $F_S$ was between $2.46{×}10^{14} Wb$ in 1906 to $4.10{×}10^{14} Wb$ in 1949, the peak of the Grand Maximum, and hence the rise in open flux was by a factor of $67{%}$.